Whole genome sequence of Lactiplantibacillus plantarum MC5 and comparative analysis of eps gene clusters - Zhao, Xuefang; Liang, Qi; Song, Xuemei; Zhang, Yan (Frontiers in Microbiology, 2023)
Probiotic MC5 can produce large amounts of exopolysaccharides (EPS) and its use as a compound fermentor can greatly improve the quality of fermented milk. To gain insight into the genomic characteristics of probiotic MC5 and reveal the relationship between its EPS biosynthetic phenotype and genotype, the strain MC5's carbohydrate metabolic capacity, sugar nucleotide-forming pathways, and EPS synthesis-related gene clusters were analyzed based on its whole genome sequence. Finally, validation tests were performed on the monosaccharides and disaccharides that the strain MC5 may metabolize. Genomic analysis showed that the MC5 had seven sugar nucleotide synthesis pathways and 11 sugar-specific phosphate transport systems (PTS), which predicted that the strain could metabolize mannose, fructose, sucrose, cellobiose, glucose, lactose, and galactose. The validation results showed that strain MC5 was able to metabolize these seven sugars and produced significant amounts of EPS (>250 mg/L). In addition, strain MC5 has 2 typical eps synthesis gene clusters, including the conserved genes epsABCDE, wzx, wzy, 6 key genes for polysaccharide biosynthesis, and 1 MC5-specific epsG gene. The above results revealed the mechanism of EPS-MC5 biosynthesis and can be used to promote the production of EPS by genetic engineering.